Effects of Working Memory Capacity on Metacognitive Monitoring: A Study of Group Differences Using a Listening Span Test - Komori, Mie (Frontiers in Psychology, 2016)
Monitoring is an executive function of working memory that serves to update novel information, focusing attention on task-relevant targets, and eliminating task-irrelevant noise. The present research used a verbal working memory task to examine how working memory capacity limits affect monitoring. Participants performed a Japanese listening span test that included maintenance of target words and listening comprehension. On each trial, participants responded to the target word and then immediately estimated confidence in recall performance for that word (metacognitive judgment). The results confirmed significant differences in monitoring accuracy between high and low capacity groups in a multi-task situation. That is, confidence judgments were superior in high vs. low capacity participants in terms of absolute accuracy and discrimination. The present research further investigated how memory load and interference affect underestimation of successful recall. The results indicated that the level of memory load that reduced word recall performance and led to an underconfidence bias varied according to participants' memory capacity. In addition, irrelevant information associated with incorrect true/ false decisions (secondary task) and word recall within the current trial impaired monitoring accuracy in both participant groups. These findings suggest that interference from unsuccessful decisions only influences low, but not high, capacity participants. Therefore, monitoring accuracy, which requires high working memory capacity, improves metacognitive abilities by inhibiting task-irrelevant noise and focusing attention on detecting task-relevant targets or useful retrieval cues, which could improve actual cognitive performance.